Relocating the Spanish Renaissance: Charles V, the Torre de la Estufa in the Alhambra, and the Islamic Past - Ripollés, Carmen (The sixteenth century journal, 2019)
This article reexamines the function, decoration, and political and artistic significance of the Torre de la Estufa of Charles V in the Alhambra, a steam room decorated between 1528 and 1539 with topographic landscapes of the conquest of Tunis and paintings of grotesques. Challenging the traditional focus on the tower’s debt to the Italian Renaissance, this essay brings attention to its pre-existing Islamic framework, arguing that its overall architectural language, specific decorative elements, and intended function reveal Charles V’s will to engage formally and conceptually with the preexisting palace as a means of advancing imperial ideology.